A randomized controlled trial of 3, 4-methylenedioxymethamphetamine (MDMA) and fear extinction retention in healthy adults. (March 2022) - Maples-Keller, Jessica L; Norrholm, Seth D; Burton, Mark; Reiff, Collin; Coghlan, Callan; Jovanovic, Tanja; Yasinski, Carly; Jarboe, Kathleen; Rakofsky, Jeffrey; Rauch, Sheila; Dunlop, Boadie W; Rothbaum, Barbara O
Background: Fear conditioning and extinction are well-characterized cross-species models of fear-related posttraumatic stress disorder (PTSD) symptoms, and recent animal data suggest that 3, 4-methylenedioxymethamphetamine (MDMA) enhances fear extinction retention. Aims: This study investigated the effect of MDMA on fear learning, extinction training, and retention in healthy humans. Methods: The study involved a randomized placebo-controlled, two-group, parallel design trial in a sample of healthy adults, age 21–55 recruited from a major metropolitan area. The experimental paradigm included a fear acquisition session followed by an extinction training session 24 hours later, and 2 hours after study drug administration. Fear extinction retention was measured 48 hours after extinction training. Participants ( N = 34; 70.6% male and 29.4% female) were randomly assigned in 1:1 ratio to 100 mg MDMA or placebo. All randomized participants completed the trial and were included in primary analyses. Safety was monitored via adverse events and vital signs. MDMA was well-tolerated with no serious adverse events. Results: Results indicated a significant main effect of session between extinction training and retention with no significant group differences. Significantly more participants in the MDMA group retained extinction learning compared to the placebo group (χ 2 = 7.29, p = 0.007). Conclusion: Although we did not observe the hypothesized facilitation of extinction retention, the findings from this initial human trial provide compelling rationale to continue to explore the potential for MDMA to impact extinction retention. Clinical Trials Registry Name and Identifier: Evaluation of MDMA on Startle Response (NCT0318176)https://clinicaltrials.gov/ct2/show/NCT03181763?term = MDMA&draw = 2&rank = 9